Exploring the Effect of Lime and Cement Ratios on the Mechanical Properties of Clay Bricks Made from Different Types of Soils - Zakarya Laouidji; Mourad Boutlikht; Abdellah Douadi; Kamel Hebbache; Elhoussine Atiki; Cherif Belebchouche; Laura Moretti; Slawomir Czarnecki (Buildings, 2025)
The clay brick industry is facing significant challenges related to improving its physico-mechanical properties and durability performance of sustainable products. The current study aimed to investigate the effect of stabilizers (lime and cement) on the clay brick properties of three soils. The investigated soils were taken from different regions of Algeria. A series of laboratory experiments were carried out to examine the effect of lime and cement addition with different ratios of 2%, 4%, 6%, 8%, and 10%, on the mechanical properties. The assessment was based on compressive strength, flexural strength, total and capillary water absorption tests. The test results showed that the lime addition to soils A and B led to a significant increase in compressive strength (CS) by 47% and 101%, respectively. The highest values obtained were for the 8% ratio. The obtained gain in compressive strength soil C reached its maximum CS at 6% ratio, and the obtained gain was 44%. However, for cement addition, the highest CS values were obtained at the 10% ratio for all studied soils. The observed gains in compressive strength for soils A, B, and C were 24%, 15%, and 33%, respectively. Flexural strength (FS) followed a similar trend, with lime addition improving (FS) by up to 400% for soil A at an 8% ratio. Cement addition also enhanced (FS), with the highest improvement of 103%, which was observed for soil A at a 10% ratio. It was also observed that lime addition significantly decreased the total absorption by up to 36% at an 8% ratio for soils A and B, and at 6% for soil C. In contrast, the total absorption decreased uniformly with the cement addition up to the 10% ratio. The lowest absorption observed at a 10% ratio was 11.95%. Lime addition also decreased the capillary absorption of clay bricks, and the lowest value was observed at an 8% ratio for both soils (A and B) and 6% for soil C. The CA values decreased by approximately 24% for soils A and B and 14% for soil C. In the case of cement addition, it was noted that the capillary absorption had the same pattern as the total absorption. The percentage decreases in CA were 41%, 40%, and 38% for soils A, B, and C, respectively. These results indicate that the enhancement of clay brick was observed for lime addition ranging from 2% to 8%. Therefore, good mechanical strengths were obtained at a 10% cement ratio.